RESPIRATORY DISEASES OF FARM ANIMALS (Archive of Conferences, 2021)
One of the direct causes of the development of respiratory diseases is the failure to comply with the necessary standards during the care and lactation of animals. Violation of the temperature-humidity system in buildings is caused by ventilation, high pollution of the air in the building with gases and dust. Damage to the respiratory system disrupts the cardiovascular, digestive, digestive, and other systems. Therefore, early detection, treatment, prevention of diseases of the respiratory system is an urgent and important task of the practice of zoology, veterinary sciences.